"Color Does Not Equal Consciousness": Educators of Color Learning to Enact a Sociopolitical Consciousness. (January 2019) - Jackson, Iesha; Knight-Manuel, Michelle
This study is based on an initiative for increasing college and career readiness for Black and Latino male high school students in New York City. From data that include 58 total hours of participant observations from 24 educators of color, written documentation from culturally relevant education–professional development (CRE-PD) activities, and transcripts of six group interviews, we examine these educators' work to further their own sociopolitical consciousness in relation to increasing Black and Latino male students' college and career readiness. We explore how secondary educators of color utilize pedagogical tools and practices in attempting to support their Black and Latino male students' navigation of particular inequities related to college knowledge and access. Our findings highlight educators' experiential knowledge as a pedagogical tool, approaches to preparing students for postsecondary opportunities, and missed opportunities to enact a sociopolitical consciousness. Recommendations for inservice educator PD and future research are discussed.